Reconstruction of Upper Eyelid Defects Secondary to Malignant Tumors with a Newly Modified Cutler-Beard Technique with Tarsoconjunctival Graft - Álvaro Bengoa-González; Bianca Ma Laslău; Agustín Martín-Clavijo; Enrique Mencía-Gutiérrez; Ma Dolores Lago-Llinás (Journal of Ophthalmology)
Purpose. We describe a modification of Cutler-Beard’s technique, using a contralateral tarsoconjunctival graft, in patients who underwent excision of large malignant tumors of the upper eyelid. Methods. This is an interventional retrospective review (clinical study) of ten cases, with age range from 64 to 86 years (mean: 71.2 years ± 6.49) with malignant upper eyelid tumors, operated by the same surgeon (AB-G), between 2011 and 2016. The resulting defects were reconstructed using a modification of Cutler-Beard’s technique. A tarsoconjunctival graft was harvested from the contralateral upper eyelid, with an extra 3 mm of conjunctiva from the superior edge of tarsus and was attached to the upper eyelid defect, different from that previously described. Follow-up ranged between 24 and 60 months (mean: 41.6 ± 9.87). Functional, cosmetic outcomes and postoperative complications were evaluated. Results. No upper eyelid retraction, eyelid margin entropion, or graft retraction was observed in any of the cases. All of the patients were satisfied with the aesthetic result. Conclusion. This technique allows us to safely inset a suitable graft on the ocular surface, with sufficient blood supply, resulting in a stable margin and good contour.